2015
DOI: 10.1186/s13195-015-0161-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurogranin and YKL-40: independent markers of synaptic degeneration and neuroinflammation in Alzheimer’s disease

Abstract: IntroductionNeuroinflammation and synaptic degeneration are major neuropathological hallmarks in Alzheimer’s disease (AD). Neurogranin and YKL-40 in cerebrospinal fluid (CSF) are newly discovered markers indicating synaptic damage and microglial activation, respectively.MethodsCSF samples from 95 individuals including 39 patients with AD dementia (AD-D), 13 with mild cognitive impairment (MCI) due to AD (MCI-AD), 29 with MCI not due to AD (MCI-o) and 14 patients with non-AD dementias (non-AD-D) were analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 50 publications
10
85
1
Order By: Relevance
“…However, the role of Nrgn is less clear in rodent models, as overexpression of Nrgn enhances spatial memory (Chaalal et al, 2014; Huang et al, 2006; Zhong et al, 2015). Controversially, recent studies have shown that elevated CSF Nrgn levels are associated with increased severity of cognitive decline (Hellwig et al, 2015; Janelidze et al, 2016; Kester et al, 2015; Portelius et al, 2015). Increased Nrgn phosphorylation has also been associated with memory impairments (Andrade et al, 2008; Kim et al, 2010; Severino et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of Nrgn is less clear in rodent models, as overexpression of Nrgn enhances spatial memory (Chaalal et al, 2014; Huang et al, 2006; Zhong et al, 2015). Controversially, recent studies have shown that elevated CSF Nrgn levels are associated with increased severity of cognitive decline (Hellwig et al, 2015; Janelidze et al, 2016; Kester et al, 2015; Portelius et al, 2015). Increased Nrgn phosphorylation has also been associated with memory impairments (Andrade et al, 2008; Kim et al, 2010; Severino et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 provides an overview of the neurogranin studies performed in CSF. Nonetheless, the results of some studies should be taken with caution owing to their small sample sizes [56,58,59,70]. Replication in larger cohorts is needed before more definitive conclusions can be made.…”
Section: The Role Of Neurogranin In Alzheimer's Diseasementioning
confidence: 91%
“…In a recent cross-sectional study, Hellwig and colleagues (2015) demonstrate that no relationships between post-synaptic damage and microglial activation are evident in AD when CSF YKL-40 and neurogranin are employed as biomarkers. However, both neurogranin and YKL-40 may be useful for the diagnosis of dementia by providing complementary information to the established core biomarkers on AD pathophysiology [70]. Table 1 provides an overview of the neurogranin studies performed in CSF.…”
Section: The Role Of Neurogranin In Alzheimer's Diseasementioning
confidence: 99%
“…On the one hand, YKL-40 immunoreactivity has been described in astrocytes located in the vicinity of senile plaques suggesting a role of YKL-40 in the inflammatory response to b-amyloid deposition (Craig-Schapiro et al, 2010); however, other studies have shown no correlation between YKL-40 and glial fibrillary acidic protein and with characteristic inflammatory molecules such as interleukin-8 (IL-8) and monocyte chemoattractant protein-1 (MCP-1) (Wennstrom et al, 2015). On the other hand, there is no clear correlatiion between YKL-40 and classical AD biomarkers (Alcolea et al, 2014(Alcolea et al, , 2015Hellwig et al, 2015;Wennstrom et al, 2015).…”
Section: Proteinsmentioning
confidence: 95%